Indigenous education as cultural preservation and appreciation of past experiences - Silva , Tais Fernanda Miranda da; Rasinski , Luana Alves; Inglez, Elisangela Ferreira (Seven Editora, 2023)
This article reports the struggle of indigenous people in search of their rights, autonomy and the valorization of their culture based on education. This way, this article stands out as a descriptive, bibliographical research of a qualitative character with the objective of understanding the social function of Education in the Indigenous environment of the Kaingang people, as a tool for the struggle for Indigenous rights and cultural knowledge preservation, in addition to presenting the importance of having indigenous teachers in this teaching modality and recognizing the right of these people to an education that respects their customs,  beliefs, languages and traditions. Data were obtained from a questionnaire made to the management team and teachers of an indigenous school in the city of Manoel Ribas. By analyzing the answers from the questionnaire, it was possible to conclude that the school contributes to indigenous thinking and to a revitalization of their culture, however, despite offering continuous training, it still suffers from a lack of indigenous teachers. DOI:https://doi.org/10.56238/sevened2023.006-002